(untitled) (Eurasian Medical Research Periodical, 2023)
An unplanned pregnancy is a pregnancy that is either unwanted or the pregnancy is mistimed. It’s also gave many factor that increase the incidence of it. To assess potential factor for unplanned pregnancy among multiparous women